2018
DOI: 10.1371/journal.pone.0195876
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal soluble FGFR3 therapy prevents the atypical development of obesity in achondroplasia

Abstract: BackgroundAchondroplasia is a rare genetic disease is characterized by abnormal bone development and early obesity. While the bone aspect of the disease has been thoroughly studied, early obesity affecting approximately 50% of them during childhood has been somewhat neglected. It nevertheless represents a major health problem in these patients, and is associated to life-threatening complications including increasing risk of cardiovascular pathologies. We have thus decided to study obesity in patients and to us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…However, BMI and other anthropometric measurements are poor predictors of body fat and fat distribution, and even more in individuals of disproportionate short stature, such as achondroplasia . In a recently published paper, the authors found an atypical obesity with preferential abdominal obesity in achondroplasia children . The obesity was not associated with classical complications, such as diabetes or hypercholesterolemia, suggesting an uncommon energy metabolism in achondroplasia .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, BMI and other anthropometric measurements are poor predictors of body fat and fat distribution, and even more in individuals of disproportionate short stature, such as achondroplasia . In a recently published paper, the authors found an atypical obesity with preferential abdominal obesity in achondroplasia children . The obesity was not associated with classical complications, such as diabetes or hypercholesterolemia, suggesting an uncommon energy metabolism in achondroplasia .…”
Section: Discussionmentioning
confidence: 98%
“…32,60,65 In a recently published paper, the authors found an atypical obesity with preferential abdominal obesity in achondroplasia children. 66 The obesity was not associated with classical complications, such as diabetes or hypercholesterolemia, suggesting an uncommon energy metabolism in achondroplasia. 66 This corresponds with previous findings by Owen et al, who found normal triglycerides and no incidents of diabetes in a cohort of adults with achondroplasia with abdominal obesity.…”
Section: Medical Complications Health Characteristics and Psychosomentioning
confidence: 94%
See 1 more Smart Citation
“…By contrast, a significant number of achondroplasia patients that carry activating FGFR3 mutations also manifest atypical obesity. 55 Difficulties that prevent drawing firm conclusions from human patients include: the germline nature of these mutations, which would additionally impact peripheral organs or indeed multiple brain regions; their rareness, which may preclude statistically valid associations with metabolic/neuroendocrine defects or diet; and their varied molecular mode of function, with some mutant receptors operating in a FGF ligand-independent manner.…”
Section: Lessons From Human Mutations and Transgenic Mouse Models Omentioning
confidence: 99%
“…The arms and legs are short, while the trunk has an almost normal size (Merker et al, ). Previous studies have reported that individuals with achondroplasia have an increased risk of obesity starting from childhood, cardiovascular disease (CVD), and mortality (Hecht et al, ; Hecht, Francomano, Horton, & Annegers, ; Paajanen, Oksala, Kuukasjarvi, & Karhunen, ; Saint‐Laurent et al, ; Wynn, King, Gambello, Waller, & Hecht, ). The reasons for this are currently unknown (Hecht et al, ; Paajanen et al, ; Wynn et al, ), but both genetic and lifestyle factors are likely involved (Hecht et al, ; Saint‐Laurent et al, ; Trenkwalder, Kessler, Schunkert, & Erdmann, ).…”
Section: Introductionmentioning
confidence: 99%